Problematyka regulacji „narzędzi hackerskich” w polskim kodeksie karnym - Brzezińska, Diana (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The „hacking tools” are the programs which constitute a real threat for the cyberspace. They allow the people without specialistic programming knowledge to commit crimes that previously were reserved only for a small group of people. This article presents the issue of regulation of the „hacker tools” in the Polish Penal Code of 1997. It points the question of interpretation of the term “the hacker tools” and discusses about the existing Polish legislation.